Opercularella lacerata - Calder, Dale R. (Zenodo, 2012)
Opercularella lacerata (Johnston, 1847) Fig. 23 Campanularia lacerata Johnston, 1847: 111, pl. 28, fig. 3. Opercularella lacerata .— Segerstedt, 1889: 14, 25.— Lönnberg, 1898: 52.— Jäderholm, 1909: 81, pl. 7, fig. 13. Campanulina lacerata .— Jägerskiöld, 1971: 61. Type locality. UK: Berwick Bay; St. Andrews (Johnston 1847: 111). Museum material. Tjärnö, floating dock at Sven Lovén Centre for Marine Sciences, 58°52’33.68”N, 11°08’43.65”E, <1 m, 07.ix.2010, collected manually, on a fucoid alga, one colony, up to 3.5 mm high, without gonophores, ROMIZ B3890. Remarks. Opercularella lacerata (Johnston, 1847) is frequent on floating docks just beneath the surface of the water on both sides of the boreal North Atlantic (personal observations), and it was found in that environment at Tjärnö. It is a euryhaline species, extending deep into the Baltic Sea (Cornelius 1995a). The boreal Opercularella pumila Clark, 1875 is somewhat similar, but its colonies are at least partly stolonal. Erect colonies of that species are more compact than those of O. lacerata and seldom have more than a half-dozen hydranths and hydrothecae per stem. Although gonophores are fixed sporosacs in both, gonothecae of O. lacerata are oval to subcylindrical while those of O. pumila are fusiform with a tapered neck (Clark 1875; Calder 1971). Also similar is Phialella quadrata (Forbes, 1848), but it differs from O. lacerata in having a medusa stage rather than fixed sporosacs. Schuchert (2001b) noted that trophosomes of O. lacerata can be distinguished from P. quadrata in having: (1) larger hydrothecae (0.3–0.5 mm vs. 0.25 mm), and (2) pedicels that are usually shorter (with five rings or less) instead of as long or longer (with more than five rings) than the hydrothecae. Other characters useful in distinguishing the two were presented by Cornelius (1995a: 176). The hydroid of Phialella quadrata has not yet been reported from southwestern Scandinavia; the report by Cornelius (1995a) that Kramp (1935b) and Rees & Rowe (1969) had recorded it from ...